The boy who made everyone laugh - Rutter, Helen (Children's author) (Scholastic Press, 2021)
Billy Plimpton wants to be a famous comedian when he grows up but his stutter is getting in the way, and right now he is so worried about being made fun of by the kids in his new school that he plans on not talking at all, but the plan backfires because his persistent silence only draws attention of the school bully--and Billy realizes that he needs another plan, one that does not depend on him speaking without a stutter.